ANALISIS PENERAPAN KURIKULUM MERDEKA DALAM MENINGKATKAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Reksiana, Reksiana (UIN Sumatera Utara Medan, 2025)
This research is motivated by the many phenomena regarding curriculum problems in Indonesia which are currently changing, but are not balanced by increasing changes in the world of education. The purpose of this study is to analyze the implementation of the Independent Curriculum in Islamic Religious Education learning at SMPN 6, South Tangerang City. The method used is descriptive qualitative research. Data collection techniques are carried out through observation, interview and documentation methods. Informants in this study were taken from people who understand the implementation of the Independent Curriculum such as: principals, curriculum representatives, Islamic Religious Education teachers, and class VII students. The data analysis technique in this study uses the Miles & Huberman data analysis technique, namely data collection, data presentation, reduction and conclusions. The findings in this study indicate that the implementation of the Independent Curriculum in Islamic Religious Education learning at SMPN 6, South Tangerang City shows an increase in creativity and love for the country for students even though there are obstacles and challenges. Teachers apply a structured approach with differentiated, project-based, and cooperative learning, as well as the use of varied learning models, such as Cooperative Learning and Project-Based Learning, supported by interactive teaching media. Meanwhile, the obstacles in its implementation are the large amount of time spent by teachers and students, and students feel burdened by the cost of making the project.